2013
DOI: 10.2485/jhtb.22.59
|View full text |Cite
|
Sign up to set email alerts
|

Low Level Fluoride Stimulates Epithelial-Mesenchymal Interaction in Oral Mucosa

Abstract: Oral mucosa consists of the superficial epithelium and the underlying lamina propria, and it functions as a barrier against exogenous substances. In development, interactions of stem/progenitor cells of the epithelium and mesenchyme are crucial to the morphogenesis of oral mucosa. Our previous work in low level fluorideinduced cell motility of epithelial cells has yielded important clues for periodontal physiology. This study focuses on a working concept of low level fluoride to provide a conducive oral enviro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…The effect of fluoride on cellular activity may be biphasic in that low concentrations provide increased osteoprogenitor cell number, whereas high concentrations are associated with histological findings of osteoblast inactivity [34]. In the present study, the use of BS and NaF to treat inflammation exhibited favorable results in agreement with previous studies [35,36]. The inhibitory effect of BS and NaF on IL‐1β, TNF‐α, and IL‐8 cytokine production was observed in IL‐1β‐treated fibroblast cells in vitro .…”
Section: Discussionsupporting
confidence: 89%
“…The effect of fluoride on cellular activity may be biphasic in that low concentrations provide increased osteoprogenitor cell number, whereas high concentrations are associated with histological findings of osteoblast inactivity [34]. In the present study, the use of BS and NaF to treat inflammation exhibited favorable results in agreement with previous studies [35,36]. The inhibitory effect of BS and NaF on IL‐1β, TNF‐α, and IL‐8 cytokine production was observed in IL‐1β‐treated fibroblast cells in vitro .…”
Section: Discussionsupporting
confidence: 89%
“…In this study, the similar responses in the PDL suggests that the effector, fluoride, is a trigger that elicits a PDL specific reaction. Although the specific mechanism of action has not been elucidated, our previous studies and the in vitro and in vivo data reported here suggest that NaF acts directly on oral cells 27,44,45) .…”
Section: Discussionmentioning
confidence: 68%
“…The cells were then treated with serum‐free medium supplemented with NaF at concentrations of 0, 50, 500, and 5 mM. Cell proliferation was assessed by the MTS assay at 12, 24, and 48 hours after NaF supplementation as per the protocol of a previously published study . Cell Titer 96® Aqueous One Solution Reagent (Promega) was added directly to each well, incubated for 2 hours, and the absorbance at 490 nm was then measured using a microplate reader (Bio‐Rad).…”
Section: Methodsmentioning
confidence: 99%
“…RNA extraction was done in BMMSCs cultured in osteoblastic induction medium with and without 50 µM NaF for 21 days as per the previously published protocol . In brief, 1 μg total extracted RNA (RNeasy Mini Kit; Qiagen KK) was reverse‐transcribed using a High‐Capacity cDNA Archive Kit (Applied Biosystems).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation